Bridging the Gap: Evaluating Hepatitis B Occupational Risk Preparedness Among Intern Doctor’s in a Bangladeshi Medical College: Hepatitis B Occupational Risk Preparedness among Intern Doctor - Hossain, Md Shakhawat; Makunnahar; anwar, Md Mahfuj ul; Jahan, Shah Md Sarwer; Chowdhury, Mohammad Shoaib; Khan, Md Masudur Rahman; Kadir, Mohammad Sofiul; Sarker, Md Mokhlesur Rahman; Salam, Farhana (Bangladesh Journal of Medicine, 2025)
Background: The incidence of HBV infection among health care workers is 2-4 times higher than general population and mostly occurred by percutaneous route. Lack of knowledge may lead to adverse professional outcome among healthcare workers in regions where the risk is high. This study was aimed to evaluate the knowledge, awareness and approach of our intern doctors towards occupational exposure of HBV in Bangladesh. Methods: This cross-sectional study was carried out on 100 working intern doctors from different departments of Rangpur medical college hospital, Bangladesh over a period of 06 months from January 2023 to June 2023. Data were collected using a self-structured questionnaire by personal interview. Results: Regarding mode of transmission of HBV, 38% of interns have overall good knowledge about HBV infection, 43% have average and 19 % have poor knowledge about HBV infection. Only 49% of interns know that both oral and injectable treatments are available for HBV infection, 76% knew that HBV has post exposure prophylaxis. In the area of practical measures for occupational safety, only 47% used sterilized instruments in every procedure and 60% of them used gloves in every procedure, 73% of them claimed needle prick or minor cut injury during their work,but only 44% took necessary measures. Only 17 interns took yearly Anti HBs titer check and 44% have full family vaccination coverage. Conclusion: The study highlights the need for better health education on safety measures to prevent infections in healthcare workers. Inadequate knowledge has led to negative attitudes towards HBV patients, impacting patient care. Bangladesh J Medicine 2025; 36(3): 116-122